Android-Based Mobile Application for the Control of Anemia in Children Aged 6 to 23 Months Old in the District of Comas – Lima - Gutiérrez Suárez, Carlos; Romero-Alva, Victor (International Journal of Child Health and Nutrition, 2023)
One of the main health problems facing the country is iron deficiency anemia. This condition reduces the level of hemoglobin present in the blood, which produces symptoms that affect the sufferer’s daily activities. According to the INEI (National Institute of Statistics and Informatics), the urban area has 36.7% of anemia, and Comas is the second district of the capital (Lima) with the second highest rate of anemia with 43.4%. This article proposes a technological solution that allows the control and prevention of iron deficiency anemia in children from 6 to 23 months old in Comas through the follow-up of the screenings performed and by improving eating habits. The result obtained was an Android-based mobile application with three navigation options. The Children option allows the registration of each screening performed and notifies the level of anemia present in the child, the Home option displays information about this condition, and the Kitchen Recipes option is responsible for enriching the child’s diet by presenting a highly nutritious recipe book, categorized according to age range. It also obtained a 90% positive acceptance rate from the sample population identified as users and patients, and a daily screening was recorded. This result can be applied to any coastal area of the country and, therefore, contributes to improving the quality of life of children by reducing anemia rates.